2021
DOI: 10.1111/jspn.12324
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a family empowerment program on asthma control and medication use in children with asthma: A randomized controlled trial

Abstract: Purpose In pediatric asthma, family empowerment education has been beneficial for the quality of life, pulmonary function, and family functioning. Few studies addressed the impact of a family empowerment program on asthma symptom control, acute healthcare use (AHCU), and medication use in children with asthma. This study aimed to assess the effect of a family empowerment intervention on asthma symptom control, AHCU, inhaler technique, and controller adherence in children with asthma. Design and Methods A singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…After a 12-month follow-up, the number of unscheduled doctors and ED visits due to asthma was reduced in the experimental and the control group. However, three child-parent education programs did not show a significant difference in ED visits and hospitalizations between the intervention and the control group at follow-up [19,20,26].…”
Section: Acute Health Care Utilizationmentioning
confidence: 75%
See 2 more Smart Citations
“…After a 12-month follow-up, the number of unscheduled doctors and ED visits due to asthma was reduced in the experimental and the control group. However, three child-parent education programs did not show a significant difference in ED visits and hospitalizations between the intervention and the control group at follow-up [19,20,26].…”
Section: Acute Health Care Utilizationmentioning
confidence: 75%
“…It was demonstrated that family education contributed to a significant decrease in asthma symptoms days and nights [15,18,20]. Indeed, family empowerment interventions were significantly effective in reducing asthma symptoms, such as coughing, wheezing, and dyspnea (p < .0001) [21], and improving asthma symptom control in school-age children (p < .001) [22,26,27]. Besides, the m-Health program of Montalbano et al was effective in improving the Child-Asthma Control Test scores (p = .0089) in the intervention group [24].…”
Section: Asthma Symptom Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have pointed out that the FCC can help improve children's awareness of the disease, reduce their shame, and effectively improve their medication compliance. 19 In the nal analysis, the level of medication compliance is still a behavioral problem. If the parents of children with higher self-management ability and self-discipline ability, the children may have higher medication compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports family empowerment interventions which is based on the family-centered nursing care philosophy. Empowerment education is a process planned to help patients and families develop the attitudes, knowledge, skills and degree of self-awareness necessary to simulate responsibility for their health-related decisions (Dardouri et al, 2021). So far, the family empowerment is used in parents of children with chronic diseases such as thalassemia, disabilities, asthma, ostomy, and psychological problems.…”
Section: Introductionmentioning
confidence: 99%